2016
DOI: 10.1016/j.jval.2015.11.015
|View full text |Cite|
|
Sign up to set email alerts
|

Systematic Review of Economic Evaluations of Units Dedicated to Acute Coronary Syndromes

Abstract: Published economic evaluations indicate that more intensive care is likely to be cost-effective in comparison to routine hospital admission for patients with suspected ACS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
2
2
0
2
Order By: Relevance
“…In the present study, the mean±SD of age (63.9±12.11 years) was significantly higher in ACS patients compared with the control group (45.47±11.75 years) with p<0.05 (Table 1). The finding is supported by the study conducted by Zaky Doaa SE et al 3 where they found the mean±SD of age for the ACS cases was 56.28±10.66 years and for the controls it was 53.1±11.47 years. The elderly has the highest incidence of cardiovascular disease and frequently present with ACS.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In the present study, the mean±SD of age (63.9±12.11 years) was significantly higher in ACS patients compared with the control group (45.47±11.75 years) with p<0.05 (Table 1). The finding is supported by the study conducted by Zaky Doaa SE et al 3 where they found the mean±SD of age for the ACS cases was 56.28±10.66 years and for the controls it was 53.1±11.47 years. The elderly has the highest incidence of cardiovascular disease and frequently present with ACS.…”
Section: Discussionsupporting
confidence: 64%
“…2 Acute coronary syndrome or Ischemic heart disease (IHD) was the main cause of death globally during the last 15 years and continues to grow at exponential rates. 3 It is an immediate threat of life and the mortality rate can be high without proper therapy and patient management. 1 The common risk factors for the disease are smoking, hypertension, diabetes, hyperlipidaemia, male sex, physical inactivity, obesity, and poor nutritional practices.…”
Section: Introductionmentioning
confidence: 99%
“…Las UDT son un área dentro del servicio de urgencias encargada de la clasificación y el tratamiento de los pacientes que consultan por dolor en el pecho o síntomas sugestivos de síndrome coronario agudo, que busca disminuir las hospitalizaciones innecesarias y evitar el alta temprana de pacientes que podrían tener un síndrome coronario agudo en curso 7,8 . Las UDT han permitido la estratificación de pacientes con dolor de pecho con el fin de iniciar tratamientos oportunos en aquellos con síndrome coronario agudo y establecer la seguridad de un alta temprana en aquellos con condiciones de bajo riesgo [8][9][10] .…”
Section: Introductionunclassified
“…Diferentes estudios reportaron que las UDT implementadas en los servicios de urgencias de los centros hospitalarios son costo-efectivas 5,6,9 y disminuyen las hospitalizaciones innecesarias 5,6 , las reconsultas a urgencias 5,6 y la morbimortalidad 11 ; sin embargo, la información disponible correspondiente a países latinoamericanos es escasa 12,13 .…”
Section: Introductionunclassified
“…Low-to-intermediate risk chest pain is a common clinical issue in emergency departments (ED) [ 1 ]. Several noninvasive tests, including coronary computed tomographic angiography (CCTA), myocardial perfusion imaging (MPI), stress electrocardiogram (ECG), and stress echocardiography, have been performed for the patients with suspected coronary artery disease (CAD), however, there has been little consensus about which testing strategy is optimal [ 2 4 ].…”
Section: Introductionmentioning
confidence: 99%